Morphological and physiological characterization of guava (Psidium guajava) under hot-arid zone of Rajasthan - SINGH, SANJAY KUMAR; MALHOTRA, S K; BHARGAVA, R; SINGH, R S; SHUKLA, ANIL KUMAR (The Indian Journal of Agricultural Sciences, 2017)
This study was carried out to investigate morpho-physiological and productivity characteristics of four genotypes of five years old guava (Psidium guajava L.) trees, grown under hot-arid zone of Rajasthan. Preliminary investigation indicated that all four cultivars of guava could survive except merely 10.0% field mortality in guava cv. L-49. The maximum increase in plant height (25.93%) and number of new leaves/branch (4.66) over six months of planting were recorded in Sweta, followed by Lalit, while during fruiting (August for rainy season guava) highest number of new shoot sprouts/branch was found in Allahabad Safeda, followed by Sweta. Lalit and Sweta also produced substantial number of new leaves/branch during fruiting, than the other cultivars. Chlorophyll a (Chla), chlorophyll b (Chlb) and total chlorophyll (Chltotal) contents were highest in L-49, followed by Lalit. The leaves produced on Sweta received lesser photosynthetically active radiations (PAR) but had highest leaf area (80.91 cm2), specific leaf area (SLA; 36.61 cm2/g) and relative water content (RWC; 60.19%). Although L-49 had thicker leaves (lowest SLA; 33. 29 cm2/g), indicating better adaptation towards resource poor environment but other cultivars of guava also had SLA at par among other three cultivars. Allahabad Safeda received maximum PAR (1066 Î¼E/m2/s), also had highest internal CO2 concentration (Ci; 207.76 Î¼mol/mol), while highest net photosynthesis rate (PN; 10.84 Î¼mol CO2/m2/s), carboxylation efficiency (CE) and water use efficiency (WUE) were observed in Lalit. Guava cv. L-49, however, showed lowest PN (6.31 Î¼mol C02/m2/s), Ci, WUE, transpiration rate (E) and CE. Thus, guava cultivars Sweta followed by Lalit performed better under hot-arid environment with better growth and physiological adaptation. L-49 was not found suitable for the area.